THE EXISTENTIAL NEGATION IN NATIVE LANGUAGES OF BRAZIL - Dallaglio Hattnher, Marize Mattos [UNESP]; Serafim, Monielly; da Silva, Vítor Henrique Santos [UNESP] (GN1 Sistemas e Publicacoes, 2023)
The so-called “existential constructions” are common to several languages around the world, although they can have quite different forms and functions. Among those languages, a specific type of marker that affirms the nonexistence of an element is verified. This phenomenon, called “existential negation”, differs from a case of predicate negation, in which a simple negation turns the sentence into a negative one. The present work analyzes existential negation in 21 native languages of Brazil, verifying i) the relationship between the existential negation form of expression (lexical or grammatical) and the form of positive existence marker; ii) the overlap between existence, location and possession. Among other results, it was possible to show that, although formal parallelism between existence and non-existence is not mandatory, the grammatical status of the expression of existential negation form always presupposes the grammatical status of the existential construction.
LA NEGACIÓN EXISTENCIAL EN LENGUAS INDÍGENAS DE BRASIL
A NEGAÇÃO EXISTENCIAL NAS LÍNGUAS NATIVAS DO BRASIL1
Keywords: existential negation; indigenous languages; location; possession; typology